Upregulation of TIMM8A is correlated with prognosis and immune regulation in BC - Zhang, Yu; Lin, Lin; Wu, Yunfei; Bing, Pingping; Zhou, Jun; Yu, Wei (Frontiers in Oncology, 2022)
Backgrounds: Breast cancer (BC) is one of the most frequently diagnosed malignancies among females. TIMM8A is upregulated in different cancer types. The purpose of this study was to elucidate the value of TIMM8A in diagnosing and predicting the prognosis of Breast Cancer (BC), and its relationship with immune cell infiltration, immune cell biomarkers, and immune checkpoints. Gene mutations, DNA methylation and pathways involved in BC were also analyzed. Methods: We downloaded the transcription profile of TIMM8A between BC and normal tissues from The Cancer Genome Atlas (TCGA). TIMM8A protein expression was assessed by the human protein map. The correlation between TIMM8A and clinical features was analyzed using R package to establish a ROC diagnostic curve. cBioPortal and MethSurv were used to identify gene alterations and DNA methylation and their effects on prognosis. The relationship between TIMM8A expression level and immune infiltration was determined by Tumor Immune Estimation Resource (TIMER) and Tumor Immune System Interaction Database (TISIDB). The CTD database was used to predict drugs that inhibit TIMM8A, and the PubChem database was used to determine the molecular structure of possible effective drugs. Results: The expression of TIMM8A in BC tissues was significantly higher than adjacent normal tissues. ROC curve analysis showed that the AUC value of TIMM8A was 0.679. Kaplan-Meier method showed that patients with high TIMM8A had a lower prognosis (Overall Survival HR = 1.83 (1.31 − 2.54), P < 0.001) than patients with low TIMM8A expression of breast cancer (148.5 months vs. 115.4 months, P < 0.001). Methylation levels at seven CpG were associated with prognosis. Correlation analysis showed that TIMM8A expression was associated with tumor immune cell infiltration. There was a significant positive correlation of TIMM8A with PDL-1, and CTLA-4 in BC. In addition, CTD database analysis identified 15 small molecular drugs that target TIMM8A, such as Cyclosporine, Leflunomide, and Tretinoin, which may be effective therapies for targeted inhibition of TIMM8A. Conclusion: In BC, up-regulated TIMM8A is significantly associated with lower survival and higher immune invasion. Our study shows that TIMM8A can be used as a biomarker for poor prognosis of BC and a potential immunotherapy target.